GAMBARAN FAKTOR RISIKO GEJALA INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA PEKERJA PT. JAKARTA CAKRATUNGGAL STEEL MILLS PULO GADUNG JAKARTA TIMUR TAHUN 2018 - Bayu Suseno; Nia Alifia Ramelan (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2020)
Workers are not only at risk of suffering from communicable and non-communicable diseases but workers can suffer from occupational diseases and / or work-related diseases. One of the occupational diseases found in PT. Jakarta Cakratunggal Steel Mills is an ARI in 2017 it shows that the incidence of ARI tends to fluctuate with the highest incidence rate in November with 51 workers showing symptoms of ARI in the production unit. The purpose of this study was to describe the risk factors for symptoms of ARI among workers in the production unit of PT. Jakarta Cakratunggal Steel Mills. This research is a descriptive study with cross sectional method. The population in this study were all workers in the production unit with a total of 117 workers. Sampling was done by simple random sampling and found a sample of 91 workers. The data used in this study are primary data and secondary data. Based on the results of the study, it was found that most of the respondents experienced mild ARI symptoms (41.8%) moderate ARI symptoms (58.2%), aged 31-40 years who experienced mild ARI symptoms (51.6%), the highest working period was 9 -16 years (38.5%) with most of them working in the steel melting unit (52.7%), most of the length of work is 8 hours / day (87.9%), the behavior of using PPE is not complete (56.0%) . The conclusion of this study is that most of the respondents experienced moderate ARI symptoms and the behavior of using Personal Protection Equipment was not good. The suggestion from this research is that workers pay more attention to K3 in doing their work.